The representation of archival document in art: analysis of the context of the use of documents in the 19th century painting preserved in the Museo del Prado (1806-1900) - Bonal Zazo, José Luis; Ortego de Lorenzo-Cáceres, María del Pilar (Revista General de Información y Documentación, 2021)
Quantitative analysis of the image of the archive document in the 19th century painting works preserved in the Museo Nacional del Prado. From the analysis of the 1974 nineteenth-century painting works collected in the Image Bank of the Prado Museum, 194 paintings were identified that included some representation of archival documents, on which, applying a content analysis methodology, the following aspects were studied: the pictorial genres in which the representation of documents is more frequent; the functional context of production of the documents represented; the documentary types reflected in the works; and the form of representation of the documents. The results allow us to conclude that in the second half of the century there was an increase in the number of documents reflected in the works and the variety of documentary types increased. Likewise, it is appreciated that there is an express intention of the authors when representing the documents, which are linked to institutional activities (executive, judicial and military) and, above all, with private activities related to the professional field and the daily life of people, which is indicative of the social projection of the documents at the time. Despite the foregoing, the document is presented as an element linked to power and, at the same time, as an element of power.